Soil potassium adsorption at several shallot center areas, Brebes Regency, Central Java Province - Arief Hartono; Desi Nadalia; Bambang Hendro Trisasongko (Brawijaya University, 2023)
Brebes Regency, Central Java, is one of Indonesia's most important shallot production center implementing intensive agriculture. In the bulb production, K is needed more than other nutrients. This study aimed to assess and describe the adsorption characteristics of K on the soils of the shallot farming system in Brebes District, Central Java. Soil samples were collected at several locations in the shallot center areas of Brebes Regency, Central Java Province. The observed soil properties included pH H2O, EC, soil texture, organic C, potential-K, exchangeable Ca, Mg, Na, and K, CEC, exchangeable Al and H, and water-soluble K. K adsorption was simulated by the Freundlich equation. The proportion of K from low to high of retention energy in the soil studied had the order, namely water-soluble K<exchangeable K<potential-K. The K adsorption result showed that the soil had a high capacity to adsorb K. It indicated that added K was accumulated in the soil. The high capacity to adsorb K indicated that K accumulated in Brebes with continuous K fertilization. This research recommended that to increase the efficiency of K fertilizer, it is necessary to introduce the technology to mine K in Brebes soils like bacteria capable of dissolving K or biofertilizers.